Role of Informal Education, and Human-Agent on Insurance Industry - Ghimire, Shurendra (Nepalese Journal of Insurance and Social Security, 2020)
This article discusses how the insured persons learn to be responsible for managing the risk via insurance and the role of agents in this process. So that, a dozen of purposively selected persons were interviewed with unstructured and open-ended questions. Interpretation of so generated qualitative information suggests that people rarely appreciate insurance, and agents are as dominant as the product in buying decisions. Employing informal education to make citizens responsible for their risk management is almost ineffective. The role of agents in enabling customers as prudent risk managers by raising their awareness about different insurance products is observed as a conflict of interests between the state and the agent. In a liberal society, persuading people by a profit-making company is dominant than the state-delivered awareness program. These findings not only question the role of the insurance agent, a human resource for facilitating people to learn about insurance, as commission-based workers instead of professional but also problematize the legitimacy of transferring the state’s responsibility of educating citizens to the private companies.